A human pilot study on positive electrostatic charge effects in solid tumors of the late-stage metastatic patients - Zandi, Ashkan; Shojaeian, Fatemeh; Abbasvandi, Fereshteh; Faranoush, Mohammad; Anbiaee, Robab; Hoseinpour, Parisa; Gilani, Ali; Saghafi, Mohammad; Zandi, Afsoon; Hoseinyazdi, Meisam; Davari, Zahra; Miraghaie, Seyyed Hossein; et al. (Frontiers in Medicine, 2023)
Background Correlative interactions between electrical charges and cancer cells involve important unknown factors in cancer diagnosis and treatment. We previously reported the intrinsic suppressive effects of pure positive electrostatic charges (PEC) on the proliferation and metabolism of invasive cancer cells without any effect on normal cells in cell lines and animal models. The proposed mechanism was the suppression of pro-caspases 3 and 9 with an increase in Bax/Bcl2 ratio in exposed malignant cells and perturbation induced in the KRAS pathway of malignant cells by electrostatic charges due to the phosphate molecule electrostatic charge as the trigger of the pathway. This study aimed to examine PECs as a complementary treatment for patients with different types of solid metastatic tumors, who showed resistance to chemotherapy and radiotherapy. Methods In this study, solid metastatic tumors of the end-stage patients (n = 41) with various types of cancers were locally exposed to PEC for at least one course of 12 days. The patient’s signs and symptoms, the changes in their tumor size, and serum markers were followed up from 30 days before positive electrostatic charge treating (PECT) until 6 months after the study. Results Entirely, 36 patients completed the related follow-ups. Significant reduction in tumor sizes and cancer-associated enzymes as well as improvement in cancer-related signs and symptoms and patients’ lifestyles, without any side effects on other tissues or metabolisms of the body, were observed in more than 80% of the candidates. Conclusion PECT induced significant cancer remission in combination with other therapies. Therefore, this non-ionizing radiation would be a beneficial complementary therapy, with no observable side effects of ionizing radiotherapy, such as post-radiation inflammation.